High Conductivity in Molecularly p‐Doped Diketopyrrolopyrrole‐Based Polymer: The Impact of a High Dopant Strength and Good Structural Order. Issue 28 (12th May 2016) - Karpov, Yevhen; Erdmann, Tim; Raguzin, Ivan; Al‐Hussein, Mahmoud; Binner, Marcus; Lappan, Uwe; Stamm, Manfred; Gerasimov, Kirill L.; Beryozkina, Tetyana; Bakulev, Vasiliy; Anokhin, Denis V.; Ivanov, Dimitri A.; et al.
Abstract : [3]‐Radialene‐based dopant CN6‐CP studied herein, with its reduction potential of +0.8 versus Fc/Fc+ and the lowest unoccupied molecular orbital level of −5.87 eV, is the strongest molecular p‐dopant reported in the open literature, so far. The efficient p‐doping of the donor–acceptor dithienyl‐diketopyrrolopyrrole‐based copolymer having the highest unoccupied molecular orbital level of −5.49 eV is achieved. The doped films exhibit electrical conductivities up to 70 S cm −1 .